2022
DOI: 10.1038/s41467-022-32831-x
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of the membrane-bound formate hydrogenlyase complex from Escherichia coli

Abstract: The prototypical hydrogen-producing enzyme, the membrane-bound formate hydrogenlyase (FHL) complex from Escherichia coli, links formate oxidation at a molybdopterin-containing formate dehydrogenase to proton reduction at a [NiFe] hydrogenase. It is of intense interest due to its ability to efficiently produce H2 during fermentation, its reversibility, allowing H2-dependent CO2 reduction, and its evolutionary link to respiratory complex I. FHL has been studied for over a century, but its atomic structure remain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 92 publications
0
23
0
Order By: Relevance
“…H 2 is dependent on the HypCD-dependent synthesis and insertion of Fe(CN) 2 CO group into the large subunit of Hyd-3, the hydrogenase component of formate hydrogenlyase complex [1,19]. Together, these observations highlight the importance of cysteine thiolates in the HypCD scaffold complex and support the role of sulfur chemistry in the maturation of Hyd [1,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 is dependent on the HypCD-dependent synthesis and insertion of Fe(CN) 2 CO group into the large subunit of Hyd-3, the hydrogenase component of formate hydrogenlyase complex [1,19]. Together, these observations highlight the importance of cysteine thiolates in the HypCD scaffold complex and support the role of sulfur chemistry in the maturation of Hyd [1,14].…”
mentioning
confidence: 99%
“…An earlier mutagenesis study demonstrated that when C69 and C72 are exchanged for alanine, the resulting E. coli strains synthesizing these variant HypD proteins failed to produce H 2 gas [ 14 ]. The ability of the formate hydrogenlyase complex to produce H 2 is dependent on the HypCD‐dependent synthesis and insertion of Fe(CN) 2 CO group into the large subunit of Hyd‐3, the hydrogenase component of formate hydrogenlyase complex [ 1 , 19 ]. Together, these observations highlight the importance of cysteine thiolates in the HypCD scaffold complex and support the role of sulfur chemistry in the maturation of Hyd [ 1 , 14 ].…”
mentioning
confidence: 99%
“…This is also the case for Escherichia coli , which can use its conjugate base, formate, as an electron source for respiration with oxygen or nitrate as an acceptor, or during fermentation, where it is imported into the cell by the formate‐nitrite transporter channel protein, FocA (Kammel et al, 2022). In the cytoplasm, formic acid is disproportionated to CO 2 and H 2 by the membrane‐associated formate hydrogenlyase (FHL) complex (Peters & Sargent, 2023; Steinhilper et al, 2022). The benefits to the cell of taking up formate are two‐fold: first, if formic acid is imported into the cell, this helps offset acidification of the cell's immediate environment (Metcalfe et al, 2022); second, if formate, rather than formic acid, is taken up and subsequently formate plus a cytoplasmic proton are converted into gaseous H 2 plus CO 2 by the FHL complex (Peters & Sargent, 2023), then this helps offset acidification of the cytoplasm and, additionally, potentially contributes to the establishment of an ion (proton) gradient (Kammel et al, 2022).…”
Section: The Importance Of Protein Interactions In Vivomentioning
confidence: 99%
“…FHL-1 and FHL-2 differ in the number and function of their respective transmembrane subunits: FHL-1 has two, while FHL-2 has five integral membrane subunits [10,[12][13][14]. This indicates different roles for these subunits in ion translocation and possibly in energy conservation [3,11,14].…”
Section: Formate Regulonmentioning
confidence: 99%
“…Both complexes are also membrane-associated and this is essential for functionality [11] and suggests an important role for the transmembrane subunits in ion translocation [10]. FHL-1 and FHL-2 differ in the number and function of their respective transmembrane subunits: FHL-1 has two, while FHL-2 has five integral membrane subunits [10,[12][13][14]. This indicates different roles for these subunits in ion translocation and possibly in energy conservation [3,11,14].…”
Section: Formate Regulonmentioning
confidence: 99%